Pengaruh Zakat Produktif, Pendapatan, dan Kinerja Amil Terhadap Kemiskinan Mustahik di Kota Banda Aceh - Nurbismi Nurbismi; Muhammad Ridha Ramli (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
Aceh Province as an area with special authority for the implementation of Islamic law, gives the authority to distribute zakat through non-structural institutions Baitul Mal Based on Qanun Number 10 of 2007. The right distribution of productive zakat is one of the targets of achievement in reducing poverty in urban areas. For this reason, the distribution of productive zakat needs to be examined in a specific study in an effort to reduce poverty in the city of Banda Aceh. This study uses multiple regression methodology by placing productive amil zakat performance as a moderating variable. which reduces poverty. Sampling was carried out as many as 100 people mustahik productive zakat in the micro business group in 2017. Based on the results of the study found that the amount of productive zakat, income, and performance of amil significantly influence the decrease of the poverty level of mustahik zakat in the city of Banda Aceh. The decline in poverty which is indicated by the income gap ratio, is able to decrease with the range of the percentage spread of 0.19% - 0.25%. So it can be concluded that the distribution of productive zakat can reduce the level of inequality in productive zakat income.